2005
DOI: 10.1029/2004gl021532
|View full text |Cite
|
Sign up to set email alerts
|

Can near‐inertial internal waves in the East Sea be observed by synthetic aperture radar?

Abstract: Near‐inertial (∼18 hours) internal waves were observed in the mid‐western part of the East Sea on May 18 and 19, 2004 using C‐band Synthetic Aperture Radar (SAR) images. Current and temperature measurements obtained during the field experiment from 10 May to 9 June 2004 (IWXES2004, Internal Wave eXperiment in the East Sea), were analyzed to investigate the processes by which near‐inertial internal waves can be seen in SAR images and how they progress. The spatial distributions of horizontal wavelength and phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…Discrimination using SAR imagery alone is thus, presently, difficult or sometimes impossible. A good example of the difficulty to discriminate between atmospheric and oceanic waves has recently become obvious in the ambiguity between SAR signatures of near-inertial internal waves and coastal lee waves in a coastal area of the Korean Peninsula (Kim et al 2005a, Zheng 2005, Kim et al 2005b.…”
Section: Introductionmentioning
confidence: 99%
“…Discrimination using SAR imagery alone is thus, presently, difficult or sometimes impossible. A good example of the difficulty to discriminate between atmospheric and oceanic waves has recently become obvious in the ambiguity between SAR signatures of near-inertial internal waves and coastal lee waves in a coastal area of the Korean Peninsula (Kim et al 2005a, Zheng 2005, Kim et al 2005b.…”
Section: Introductionmentioning
confidence: 99%
“…Non‐linear internal waves (NLIWs) evolved from internal tides are common in many coastal regions [e.g., Holloway et al , 1997; Zhao et al , 2004]. However, off the east coast of Korea, several studies have reported NLIWs originating only from wind‐induced near‐inertial (17–20 hours) internal waves [ Nam et al , 2007; D. J. Kim et al , 2005; H. J. Kim et al , 2005; Kim et al , 2001]. This seems to be due to the weak barotropic tides (∼5 cm) in the East (Japan) Sea, about ten times less than those in the shallow Korea Strait (KS) [ Park et al , 2006].…”
Section: Introductionmentioning
confidence: 99%
“…Undular patterns on two ENVISAT ASAR images taken over the eastern coastal area of the Korean Peninsula on May 18–19, 2004 were interpreted as shoreward propagating near‐inertial ocean internal waves by Kim et al [2005]. The link between the undular patterns and near‐inertial ocean internal waves the authors found, is a phenomenal wave phase speed of 0.3 ms −1 , which was directly estimated from the two successively acquired SAR images.…”
mentioning
confidence: 92%
“…Meanwhile, a long and narrow mountain valley can channel and force the katabatic airflow to converge, causing the katabatic wind to strengthen. The SAR‐imaged eastern Korean Peninsula area satisfies all favorable conditions for the katabatic wind formation: mountainous topography with many peaks from 1300 m to 1700 m and steep shore, favorable season (May, local spring), favorable timing (local midnight and early morning), and favorable offshore wind of 3 to 4 ms −1 [ Kim et al , 2005]. Furthermore, on the SAR images, one can see apparent offshore jet‐like patterns with axes perpendicular to the coastline distributed between 37°N and 39°N (five on Kim et al 's [2005] Figure 2a in bright, and four on Kim et al 's [2005] Figure 2b in dark, respectively).…”
mentioning
confidence: 99%